Psychometric evaluation of PHQ–9 and GAD–7 among community health volunteers and nurses/midwives in Kenya following a nation-wide telephonic survey - Odero, Sabina Adhiambo; Mwangi, Paul; Odhiambo, Rachel; Mumbua Nzioka, Brenda; Shumba, Constance; Ndirangu-Mugo, Eunice; Abubakar, Amina (Frontiers in Psychiatry, 2023)
Abstract Background: Nurses/midwives and Community Health Volunteers (CHVs) are exposed to chronic stressors putting them at risk of developing mental health problems. This has been exacerbated by the COVID-19 pandemic. There is limited empirical evidence of the burden of mental health problems among health care workers partly due to the lack of adequately standardized and validated measures for use among health care workers in Sub-Saharan Africa. This study aimed to perform the psychometric evaluation of the PHQ-9 and GAD-7 administered to nurses/midwives and CHVs across 47 counties in Kenya. Methods: Between June and November 2021, a national survey on mental well-being and resilience among nurses/midwives and CHVs was conducted via telephone interviews. The survey had a total sample size of 1907 nurses/midwives and 2027 CHVs. Cronbach's alpha and MacDonalds' omega were used to evaluate the scale's internal consistency. Confirmatory Factor Analysis (CFA) was used to test the one-factor structure of the scales. Multi-group CFA was applied to evaluate the generalizability of the scales across the Swahili and English versions, and among male and female health workers. The Spearman correlation was used to assess the tools' divergent and convergent validity. Results: The internal consistency of PHQ-9 and GAD-7 was good, with alpha and omega values above 0.7 across study samples. CFA results indicated a one-factor structure of the PHQ-9 and GAD-7 for both nurses/midwives and CHVs. Multi-group CFA showed that both scales were unidimensional across both language and sex. The PHQ-9 and GAD-7 were positively correlated with perceived stress, burnout, and post-traumatic stress disorder, indicating convergent validity. The PHQ-9 and GAD-7 were also significantly positively correlated with resilience and work engagement, supporting divergent validity. Conclusion: The PHQ-9 and GAD-7 are unidimensional, reliable, and valid tools for screening depression and anxiety among nurses/midwives and CHVs. The tools can be administered in a similar population or study setting using either Swahili or English.